Penyelesaian Sengketa Kredit Macet Melalui Pelaksanaan Pelelangan Aset Debitur Oleh PT. Bank Artha Graha Internasional, Tbk Medan - Michael Willy Chandra; Sutiarnoto Sutiarnoto; Ida Nadirah (DE LEGA LATA: JURNAL ILMU HUKUM, 2020)
Financial institutions as one of the financial institutions have a strategic position because they participate in the provision of funds or credit needed to finance activities in the financial sector, besides that it is still a primary source of funds for everyone. Banks in the framework of this agreement often take steps to auction assets. The research method used is the type of normative legal research. Problems raised in this study, namely regarding the position of the debtor's assets as collateral in the credit agreement, the process of settlement of bad debts through the implementation of the debtor's asset auction, and auctioning auction assets related to Bank Artha Graha Internasional, Tbk Medan. The results showed that the existence of the debtor's assets as collateral in a credit agreement with PT. Bank Artha Graha Internasional, Tbk. Medan is used to settle bad credit disputes which is a bank's help to take repayment of credit agreements with the sale of assets of the debtor's guarantee through the auction auction method based on Law Number 4 of 1996.